Effects of fecal microbiota transplantation from yaks on weaning diarrhea, fecal microbiota composition, microbial network structure and functional pathways in Chinese Holstein calves - Li, Yuanyuan; Li, Xin; Wu, Yanyan; Zhang, Wenju (Frontiers in Microbiology, 2022)
This study was conducted to investigate the effect of fecal microbiota transplantation on weaning diarrhea, fecal microbiota composition, microbial network structure and functional pathways of calves. In this study, 50 Chinese Holstein calves were randomly divided into five groups of 10 each: NC group (no supplementation), Control group (normal saline), low concentration FMT group (LFMT, 1×108 CFU/mL), high concentration FMT group (HMFT, 1×109 CFU/mL ), and sterilized FMT group (SMFT, sterilized bacterial solution). The test lasted for 30 days.We found that FMT reduced the incidence of diarrhea in weaned calves, and the anti-diarrhea effect of LFMT was stronger than those of HFMT and SFMT. Calf feces were collected by rectal palpation on days 5, 10, 15, and 20 post-weaning, and high-throughput sequencing of bacterial 16S rRNA and fungal internal transcribed spacer region of fecal microbiota was performed. We observed that the richness and diversity of bacterial flora in the LFMT, HFMT, and SFMT groups were higher than those in the NC and Control groups at day 20 after weaning. The treatment had a significant effect on bacterial richness (P < 0.05), but not on fungal diversity or richness. The analysis of gut microbiome showed that Firmicutes and Bacteroides were the main bacterial phyla in the feces of weaned calves, and norank_ f Muribaculaceae, UCG-005, Rikenellaceae_RC9_gut_group, Bacteroides, and Blautia were the main genera. Ascomycota and Basidiomycota were the main fungal phyla. Compared to abundance parameters in the Control and NC groups, relative abundances of Firmicutes in the FMT groups increased at different time points after weaning. The relative abundance of Blautia and Lactobacillus in the LFMT group increased significantly after weaning. In addition, abundances of Ruminococcus and Romboutsia, which produce short-chain fatty acids, were also increased in different FMT groups. FMT significantly increased the relative abundance of beneficial bacteria, enhanced the complexity of the fecal microbial network, and promoted important metabolic and cellular processes in weaned calves. In conclusion, our study provides a reference and theoretical basis for FMT in the treatment and prevention of calf weaning diarrhea and other intestinal diseases in ruminants.